Bioprinting: Microfluidics‐Enabled Multimaterial Maskless Stereolithographic Bioprinting (Adv. Mater. 27/2018). Issue 27 (2nd July 2018) - Miri, Amir K.; Nieto, Daniel; Iglesias, Luis; Goodarzi Hosseinabadi, Hossein; Maharjan, Sushila; Ruiz‐Esparza, Guillermo U.; Khoshakhlagh, Parastoo; Manbachi, Amir; Dokmeci, Mehmet Remzi; Chen, Shaochen; Shin, Su Ryon; Zhang, Yu Shrike; et al.
Abstract : A stereolithography‐based bioprinting platform for multimaterial fabrication of heterogeneous tissue constructs is developed in article number1800242, by Yu Shrike Zhang, Ali Khademhosseini, and co‐workers. This is realized through dynamic patterning by a digital micro‐mirror device synchronized by a moving stage and a microfluidic device containing digitally controllable pneumatic valves. The system provides a robust platform for bioprinting of high‐fidelity microstructures on‐demand for numerous biomedical applications, otherwise not readily achievable at high speed with conventional stereolithographic biofabrication techniques.